Sleep patterns and cardiovascular disease risk in US participants: a comprehensive analysis - Wu, Yue; Li, Zhizheng; Zhao, Peng; Xu, Jiajing; Yuan, Min (Frontiers in Neuroscience, 2025)
Background and purposeTo evaluate the association between sleep-related factors, including sleep duration, self-reported sleep disturbances, and diagnosed sleep disorders, and the risk of cardiovascular disease (CVD) in US participants.MethodsThe data of this study from the National Health and Nutrition Examination Survey (NHANES) conducted between 2007 and 2014. Sleep factors were assessed using a standardized questionnaire, and overall sleep scores were calculated on a scale of 0 to 3. The participants were classified into three sleep pattern groups: poor sleep pattern (overall sleep score ≤ 1), intermediate sleep pattern (overall sleep score = 2), and healthy sleep pattern (overall sleep score = 3). CVD was defined based on self-reported questionnaire responses. Logistic regression models were used to investigate the association between sleep factors and CVD.ResultsAmong 21,115 participants, 2,245 (10.6%) were diagnosed with CVD. Participants with poor sleep patterns had a significantly higher risk of CVD (OR = 1.82, 95% CI: 1.52–2.16, p < 0.001). Self-reported trouble sleeping (OR = 1.53, 95% CI: 1.32–1.78, p < 0.001), and sleep disorder (OR = 2.09, 95% CI: 1.75–2.50, p < 0.001) were related to an increased risk of CVD. However, no such association was observed for either short (OR = 1.12, 95% CI: 0.95–1.33, p = 0.174) or long sleep durations (OR = 1.14, 95% CI: 0.90–1.45, p = 0.266). Our study also suggested an interaction between sleep patterns and age (P for interaction = 0.002).ConclusionThis study highlights the significant association between poor sleep patterns and an increased risk of CVD in US participants.